Sådan fortæller man, at man får et barn. Diskursive onlinekonstruktioner - Grønning, Anette (K&K - Kultur og Klasse, 2012)
HOW TO TELL THAT YOU ARE PREGNANT | The focus of this article is mediated exposure of life before life based on fetal images, including textual updates uploaded to individual Facebook profiles. The article analyses how pictures of embryos have become part of daily digital self presentation and the narrative about expecting a child. We follow a pregnant’s Facebook profile from the moment she uploads the first fetal image around the twelfth week, till the moment she updates with the news about the delivery documented by a picture of her newborn baby. The mediated exposure also involves the coming father, as the pregnant woman tags the pictures with his name to underline the family ties. Many relations (mostly women) contribute with comments that can be categorised into three groups: serious, humoristic-ironic and analysing questioning. The Facebook update can be seen as a side stage or middle region (Meyrowitz) position, a constantly more muddy space between public and private self presentation. This new praxis confirms Jean Baudrillard’s thoughts about the subject’s exaggerated presentation of self. The online audience is more comprehensive and less controllable than offline. The pregnant exposes her pregnancy, motherhood and her product (the foetus) through updates, pictures and tagging. The Facebook update is a new way to interpellate family relations and to celebrate the coming new member with the comprehensive network in three levels.